Gender Differences in the Levels of Posttraumatic Stress Disorder Resulting from 2007/2008 Post Election Violence among Primary School Pupils in Kibera and Kayole Settlements, Nairobi, Kenya - Mwania, Jonathan Muema; Muola, James Muthee (Contemporary Research Center Australia, 2014)
This study sought to determine whether there were significant gender differences in the levels of posttraumatic stress disorder resulting from the post election violence among primary school children in Kenya. The target population includes all the standard seven pupils in six primary schools in Kibera and Kayole settlements. A proportionate random sample of 164 pupils in each location was selected to participate in the study. Three instruments were used to collect data. These were the Personal Experiences during Post Election Violence questionnaire, Psychological Stability Scale, and Post Traumatic Experience Psychological Scale. Although the study revealed high levels of PTSD among the affected pupils, there were no significant gender differences in the level of PTSD. It was recommended that there should be a provision for enhanced parent-teacher communications and there be available school psychologists and counselors trained in family intervention within the school setting. These are basic requirements for successful intervention and treatment of childhood posttraumatic stress disorder. The establishment of school-based programs from early childhood onward that teach conflict resolution, emotional literacy, and anger management skills is also desirable.
Keywords: Violence; Trauma; Posttraumatic Stress Disorder; Psychological Stability